2016
DOI: 10.1038/srep35535
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Boron Nitride With High Water Dispersibility For Boron Neutron Capture Therapy

Abstract: Highly water dispersible boron based compounds are innovative and advanced materials which can be used in Boron Neutron Capture Therapy for cancer treatment (BNCT). Present study deals with the synthesis of highly water dispersible nanostructured Boron Nitride (BN). Unique and relatively low temperature synthesis route is the soul of present study. The morphological examinations (Scanning/transmission electron microscopy) of synthesized nanostructures showed that they are in transient phase from two dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 60 publications
4
86
0
1
Order By: Relevance
“…Furthermore, peaks at 1020, 1160, and 1672 cm −1 were consistent with C-O, B-N-O, and C=O bond, respectively [44]. Another peak centered at 3187 cm −1 corresponds to the B-OH bond [45,46].…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, peaks at 1020, 1160, and 1672 cm −1 were consistent with C-O, B-N-O, and C=O bond, respectively [44]. Another peak centered at 3187 cm −1 corresponds to the B-OH bond [45,46].…”
Section: Resultsmentioning
confidence: 80%
“…It is notable that the OH peak at 400 nmeV is offset from the expected energy of ≈420 meV, while the OD peak clearly matches its expected value. A wide band of NH and NH 2 stretching modes has been recorded in the energy range between 372 and 409 meV using monochromated EELS and in optical spectroscopy and there is a possibility that some NH x , with a resonance of ≈400 meV, has adsorbed on the BN surface during the sample preparation . However, we expect this effect to be very small due to its low concentration with respect to water.…”
mentioning
confidence: 99%
“…Singh and co-workers [ 51 ] tested the biocompatibility of boron nitride in the context of Boron Neutron Therapy (BNCT). The nanostructured BN was added to various cell line cultures: HeLa, HEK-293 and MCF-7 in the concentration range of 0.25–1.0 mg mL −1 and incubated for 24 and 48 h to determine the cellular response.…”
Section: Discussionmentioning
confidence: 99%
“…Cell survival rate was the lowest after 48-h incubation and reached 40% for MCF-7 and 30% for HeLa cells at the 2 mg mL −1 concentration. HEK-293 cells exhibited by 50% higher survival rate during 48-h incubation and by 70% during 24-h exposure at 2 mg mL −1 concentration, thus Singh et al [ 51 ] concluded that the cytotoxicity of BN nanostructures was higher for cancerous cells in comparison with normal cell lines [ 50 ]. Singh et al [ 51 ] suggested that a higher membrane pore size might be responsible for the enhanced uptake of BN, which led to a higher cytotoxicity, but these conclusions were not validated and need to be evaluated in further investigations [ 51 ].…”
Section: Discussionmentioning
confidence: 99%